(untitled) (Journal of Medical & Health Sciences Review, 2025)
Parkinsonism is a neurodegenerative disorder characterized by bradykinesia, resting tremor, rigidity, and postural instability. These motor symptoms, especially tremors, can be unpredictable and fluctuate with changes in emotional or physical state, posing unique intraoperative challenges. In ophthalmic surgery—where precision and patient stillness are critical—managing Parkinsonian symptoms becomes particularly important. We report the case of a 68-year-old female with a known diagnosis of Parkinsonism who was scheduled for cataract extraction under local anesthesia. Her tremors were well-controlled preoperatively, and she had no other systemic comorbidities or anesthetic contraindications. However, upon being positioned for surgery and administration of local anesthesia, she developed re-emergent, severe tremors that significantly impaired surgical visualization and jeopardized intraocular safety. Despite attempts at verbal reassurance and supportive measures, the motor instability persisted. A prompt decision was made to convert to general anesthesia, which resulted in effective tremor suppression and allowed the procedure to be completed without complication. Such scenarios are not uncommon in ophthalmic operating rooms, particularly among elderly patients with neurological disorders. This case highlights the importance of understanding the pathophysiology of Parkinsonism, recognizing the potential for intraoperative motor fluctuations even when preoperative control seems adequate, and being prepared to adjust anesthetic strategy accordingly. General anesthesia may be a safer primary option in selected Parkinsonism patients where motor unpredictability can interfere with surgical outcomes. Through this case, we emphasize the need for close preoperative evaluation, anesthetic adaptability, and multidisciplinary planning between ophthalmologists and anesthetists. Understanding the clinical features, behavioral triggers, and perioperative risks of Parkinsonism is crucial for delivering safe and effective ophthalmic care.